2017
DOI: 10.1080/16546628.2017.1364117
|View full text |Cite
|
Sign up to set email alerts
|

Anti-diabetic activity of stigmasterol from soybean oil by targeting the GLUT4 glucose transporter

Abstract: The present study investigated the anti-diabetic activity and potential mechanism of stigmasterol (SMR), which is a kind of phytosterols derived from the edible soybean oil in vitro and in vivo. SMR displayed a mild GLUT4 translocation activity by 1.44-fold in L6 cells. L6 cells were treated with different concentration of SMR, showing significant effects on the enhancing glucose uptake. SMR administrated orally to the KK-Ay mice significantly alleviated their insulin resistance and oral glucose tolerance with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(58 citation statements)
references
References 52 publications
(53 reference statements)
1
49
0
1
Order By: Relevance
“…Other research groups reported reduced abdominal, visceral, and subcutaneous fat after phytosterols consumption in healthy subjects, without imposing adverse events such as reduced serum fat‐soluble vitamins levels (Saito et al, ; Takeshita et al, ). Improving insulin sensitivity and glucose metabolism after PS supplementation (Wang et al, ; Xiong et al, ) also has been reported. Expression and translocation of glucose transporter 4 in the skeletal muscle, white adipose tissue, and liver reported to be increased after PS supplementation (Subash‐Babu, Ignacimuthu, & ALSHATWI, ; Xiong et al, ).…”
Section: Discussionmentioning
confidence: 86%
“…Other research groups reported reduced abdominal, visceral, and subcutaneous fat after phytosterols consumption in healthy subjects, without imposing adverse events such as reduced serum fat‐soluble vitamins levels (Saito et al, ; Takeshita et al, ). Improving insulin sensitivity and glucose metabolism after PS supplementation (Wang et al, ; Xiong et al, ) also has been reported. Expression and translocation of glucose transporter 4 in the skeletal muscle, white adipose tissue, and liver reported to be increased after PS supplementation (Subash‐Babu, Ignacimuthu, & ALSHATWI, ; Xiong et al, ).…”
Section: Discussionmentioning
confidence: 86%
“…Stigmasterol was anti-diabetic, WARD et al [42] found that stigmasterol could improve the increase of free cholesterol caused by glucolipid toxicity in insulinoma cells (INS-1), which led to defects in insulin secretion, increased total insulin, and promoted stimulus protein recombination and also had been shown that played a bene cial role in the treatment of T2DM. Wang et al [43] found that in vitro experiments, treating of L6 cells with different concentrations of stigmasterol had a signi cant effect on promoting glucose uptake. In the in vivo test, after oral administration of stigmasterol, fasting blood glucose levels and blood lipid indexes (such as triacylglycerol and cholesterol) in KK-AY mice were signi cantly reduced, which signi cantly reduced insulin resistance and oral glucose tolerance in KK-AY mice.…”
Section: Discussionmentioning
confidence: 99%
“…In skeletal muscle, insulin stimulation induces translocation of GLUT4 from intracellular vesicles within the cytoplasm to the plasma membrane and thereby increases glucose uptake [18,19]. When insulin levels decrease in the blood and insulin receptors are no longer occupied, the glucose transporters are recycled back into the cytoplasm.…”
Section: Glucose Metabolism In Skeletal Musclementioning
confidence: 99%